Heteronormativity and prostate cancer: A discursive paper. Issue 1 (28th July 2017) - Kelly, Daniel; Sakellariou, Dikaios; Fry, Sarah; Vougioukalou, Sofia
Abstract : Aims and objectives: To discuss the risks that heteronormative assumptions play in prostate cancer care and how these may be addressed. Background: There is international evidence to support the case that LGBT patients with cancer are less likely to report poor health or self‐disclose sexual orientation. Gender‐specific cancers, such as prostate cancer, require particular interventions in terms of supportive care. These may include advice about side‐effect management (such as incontinence or erectile dysfunction), treatment choices and social and emotional issues. In this paper, we discuss and analyse the heteronormative assumptions and culture that exist around this cancer. We argue that this situation may act as a barrier to effective supportive care for all Lesbian women, Gay, Transgender and Bisexual patients, in this case men who have sex with men. [Correction added on 21 September 2017, after first online publication: The first sentence of the Background section has been revised for clarity in this current version.] Design: Theoretical exploration of heteronormativity considered against the clinical context of prostate cancer. Methods: Identification and inclusion of relevant international evidence combined with clinical discussion. Results: This paper posits a number of questions around heteronormativity in relation to prostate cancer information provision, supportive care and male sexuality. While assumptions regarding sexual orientation should be avoided in clinical encounters, this may be difficult when heteronormative assumptions dominate. Existing research supports the assertion that patient experience, including the needs of LGBT patients, should be central to service developments. Conclusion: Assumptions about sexual orientation should be avoided and recorded accurately and sensitively, and relational models of care should be promoted at the start of cancer treatment in an appropriate manner. These may assist in reducing the risks of embarrassment or offence to nonheterosexual patients, or to professionals who may adopt heteronormative assumptions. Relevance to clinical practice: Having an awareness of the risks of making heteronormative assumptions in clinical practice will be useful for all health professionals engaged in prostate cancer care. This awareness can prevent embarrassment or upset for patients and ensure a more equitable provision of service, including men with prostate cancer who do not identify as heterosexual.